Inconsistencies in the planning of the duration of anticoagulation among outpatients with acute deep-vein thrombosis - Spirk, David; Husmann, Marc; Willenberg, Torsten; Banyai, Martin; Frank, Ulrich; Baldi, Thomas; Amann-Vesti, Beatrice; Baumgartner, Iris; Kucher, Nils (Thrombosis and Haemostasis, 2011)
Three-month anticoagulation is recommended to treat provoked or first distal deep-vein thrombosis (DVT), and indefinite-duration anticoagulation should be considered for patients with unprovoked proximal, un-provoked recurrent, or cancer-associated DVT. In the prospective Out-patient Treatment of Deep Vein Thrombosis in Switzerland (OTIS-DVT) Registry of 502 patients with acute objectively confirmed lower extremity DVT (59% provoked or first distal DVT; 41% unprovoked proximal, unprovoked recurrent, or cancer-associated DVT) from 53 private practices and 11 hospitals, we investigated the planned duration of anticoagulation at the time of treatment initiation. The decision to administer limited-duration anticoagulation therapy was made in 343 (68%) patients with a median duration of 107 (interquartile range 91–182) days for provoked or first distal DVT, and 182 (interquartile range 111–184) days for unprovoked proximal, unprovoked recurrent, or cancer-associated DVT. Among patients with provoked or first distal DVT, anticoagulation was recommended for <3 months in 11%, ≥3 months in 63%, and for an indefinite period in 26%. Among patients with unprovoked proximal, unprovoked recurrent, or cancer-associated DVT, anticoagulation was recommended for <6 months in 22%, 6–12 months in 38%, and for an indefinite period in 40%. Overall, there was more frequent planning of indefinite-duration therapy from hospital physicians as compared with private practice physicians (39% vs. 28%; p=0.019). Considerable inconsistency in planning the duration of anticoagulation therapy mandates an improvement in risk stratification of outpatients with acute DVT.
Keywords: Deep-vein thrombosis; anticoagulants; outpatient treatment